2002
DOI: 10.21273/hortsci.37.4.693
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Propagation of Three Species of Columnar Cacti from the Sonoran Desert

Abstract: In vitro propagation systems were developed for Carnegiea gigantea (Engelm.) Britt & Rose, Pachycereus pringlei (Berger) Britt & Rose and Stenocereus thurberi (Engelm.) Buxb, three North American species of columnar cacti. In vitro germinated seedlings were used as a source of explants. Multiple shoot formation from areoles was achieved for three types of explants (apical, lateral, and transverse) cultured on Muras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Coryphantha macromeris was maintained on semisolid Murashige and Skoog medium [ 69 ] (3% sucrose, 8 g·L −1 agar, and pH 5.7) and incubated at 25 °C with fluorescent light (40 μmol·m 2 ·s −1 ) and 16/8 (light/dark) photoperiod. Each plant was subcultured for three months during one year with the described conditions, and then in vitro plants were acclimated to greenhouse conditions as reported previously [ 26 ] and kept for one year until harvesting for phytochemical analysis. The plant material was botanically identified by Professor Miguel Alvarado Rodríguez.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coryphantha macromeris was maintained on semisolid Murashige and Skoog medium [ 69 ] (3% sucrose, 8 g·L −1 agar, and pH 5.7) and incubated at 25 °C with fluorescent light (40 μmol·m 2 ·s −1 ) and 16/8 (light/dark) photoperiod. Each plant was subcultured for three months during one year with the described conditions, and then in vitro plants were acclimated to greenhouse conditions as reported previously [ 26 ] and kept for one year until harvesting for phytochemical analysis. The plant material was botanically identified by Professor Miguel Alvarado Rodríguez.…”
Section: Methodsmentioning
confidence: 99%
“…are slow growing plants and the environmental conditions of semiarid regions make their germination, growth, and reproduction difficult; for this reason, biotechnological approaches have been proposed for the in vitro propagation of Coryphantha spp. and other cacti species [ 26 , 27 ]. Coryphantha macromeris (Engelm.)…”
Section: Introductionmentioning
confidence: 99%
“…After 5 weeks of culture, the seedlings that developed roots were removed carefully from the culture medium and washed with distilled water. The in vitro plants were then transferred into pots containing substrate (PROMIX ® , United States) and acclimated to greenhouse conditions as reported previously (Pérez-Molphe-Balch et al, 2002). Each pot was covered with a transparent polythene bag for 2-3 weeks to prevent desiccation and allow acclimatization.…”
Section: Plant Materialsmentioning
confidence: 99%
“…In fact, it was observed that media formulations including agar at g L -1 hindered radicle penetration just after germination (Figure 2), causing developmental delay with respect to those grown with 8 g L -1 . Furthermore, high concentration of gelling agents may decrease the amount of available water (Pérez- Molphe-Balch et al, 2002;Garcia-Osuna et al, 2011), affecting adversely seedling development. These findings may also explain why media M4 and M8, with the highest sucrose and agar levels, showed the poorest values in general, particularly in the most advanced stages (i.e.…”
Section: <Table 3>mentioning
confidence: 99%